Changing the Architectural Role - By Implementing Early Cost Estimations - JOHANSSON, ELLINOR; Johansson, Emma (My University, 2016)
Cost estimation has been stated to be an essential part of all construction projects. Today cost estimates are performed in different stages by different actors, however, it is generally not a part of the architectural practice. In the design phase, each change in choice of design will impact the total project cost, but despite this, architects have been seen to be poor at being cost aware. It has further been stated in research that cost estimates are made too late in projects, which often leads to compromises being made on the design later on. Further, research on cost estimates in projects raising the architect focus and perspective is limited. This study sets out to investigate this gap, and looks at cost estimations from the architect perspective. Among the different existing methods and tools for cost estimations, are ones based on Building Information Modeling (BIM). However, it has been questioned whether all available tools are applicable for early stages of projects, and further for the architect profession. The main objectives of this study have been to identify the values and challenges for architects in performing cost estimations in the early design phase, and to identify whether BIM could impact or support this. Consequently, if new cost estimation processes or practices within an architectural firm are to be implemented, there are factors important to consider. Therefore, this study looks at implementation management, including barriers and challenges one might be facing. This study can be especially valuable for architect firms looking to see how their practices could develop. The research methodology included a theoretical review, as well as a case study at an architectural firm where 11 semi-structured interviews were conducted. Additionally, interviews were held with two clients of the architect firm. Main findings of this study include that there are many values in architect firms performing cost estimates and simultaneously raising their overall cost awareness. BIM was concluded to be able to support in this context. However, there were also challenges found in this context; some specifically related to architects being able to do such, some concerning the internal processes, and others more general. The values of these cost estimates were concluded to be largest internally for the architect firm itself. However, findings suggest that winnings can be concluded to exist also on the broader perspective, by increasing the project cost dialogue between all parties involved on the project and leading to overall better project outcomes.
Keywords: Samhällsbyggnadsteknik; Civil Engineering